ショウワキチ ノ ジシン カンソク - 神沼, 克伊; カミヌマ, カツタダ; 江頭, 庸夫; エトウ, ツネオ; 吉田, 光雄; ヨシダ, ミツオ; KAMINUMA, Katsutada; ETO, Tsuneo; YOSHIDA, Mitsuo (国立極地研究所, 1968)
P(論文) The seismological observation at Syowa Station was begun in 1959 by the 3rd party of JARE (Japanese Antaictic Research Expedition) using a HES seismograph of Z component In 1961, adding HES seismographs of two horizontal components, the seismological obsetvation at Syowa Station was carried out with a three component seismograph Since 1966, the observations have been continued by JARE, using HES seismographs of three components The period of pendulum is 1 0 second and that of galvanometer is also about 1 0 second In 1967, a three component long-period seismograph was installed at Syowa Station. The period of pendulum was 15 0 seconds and that of galvanometer was about 1 0 second Using an amplifier between the pendulum and the galvanometer, we get the same characteristics of amplitude and phase as the long-period seismograph operated by USCGS But there were many troubles in the system, and we could not get satisfactory data In 1968, the long-period seismographs have been operated without an amplifier Theie are many pioblems in operating long-period seismographs in Antarctica departmental bulletin paper